2022
DOI: 10.1155/2022/5559470
|View full text |Cite
|
Sign up to set email alerts
|

LC-MS-Based Lipidomic Analysis of Serum Samples from Patients with Type 2 Diabetes Mellitus (T2DM)

Abstract: Background. With the development of social economy, type 2 diabetes mellitus (T2DM) is becoming a severe health problem globally. Methods. To systematically understand the lipid metabolism in T2DM, we applied untargeted lipidomics to the serum of T2DM patients and control group using ultrahigh-performance liquid chromatography (UHPLC) coupled with high-resolution mass spectrometry (MS). Results. Over two thousand molecular features were detected by our approach, of which 222 lipid species in positive ion mode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 62 publications
2
10
0
Order By: Relevance
“…Cancer is the second largest cause of death worldwide with an overall incidence rate of 20.2% over a human lifetime 164 . It has been shown that lipid metabolism in cells is drastically elevated during the different stages of cancer development 165–167 . Increased lipids are needed for plasma membrane synthesis and energy production, but also influence cell membrane compositions to favour metastasis and trigger signalling events within cancer cells.…”
Section: In Review: Results and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Cancer is the second largest cause of death worldwide with an overall incidence rate of 20.2% over a human lifetime 164 . It has been shown that lipid metabolism in cells is drastically elevated during the different stages of cancer development 165–167 . Increased lipids are needed for plasma membrane synthesis and energy production, but also influence cell membrane compositions to favour metastasis and trigger signalling events within cancer cells.…”
Section: In Review: Results and Discussionmentioning
confidence: 99%
“…Due to the elevated risk of mortality with these diseases, there is a need for strategies in its identification, prevention, and treatment within healthcare. In 2022, as evidenced in Figure 5, the bulk of research articles focussed on related diseases: CVD, 232–255 diabetes, 166,233,249,250,256–278 liver disease, 51,279–293 MetS 277,294,295 and obesity 277,295–305 …”
Section: In Review: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations